The IMF and Russia in the 1990's - Odling-Smee, John (IMF Working Papers; Working Paper ;, 2004)
This paper explains the IMF's impact on economic policies in Russia, focusing on where the IMF made a difference. The Russian economic and political leadership essentially determined economic policies. The IMF's influence was modest: it had only a limited impact on overall fiscal policy and the major structural reforms, but it had a positive impact on monetary policy. A tougher position on fiscal policy in 1996-98 might have produced a better outcome. The G-7's concerns weakened the IMF. However, the IMF played a major role in transferring knowledge about macroeconomic policymaking and implementation.